Air pollution and climate change impact on forest ecosystems in Asian region – a review. Issue 1 (31st December 2022) - Sonwani, Saurabh; Hussain, Sharfaa; Saxena, Pallavi
ABSTRACT: Forests are complex ecosystems comprising various trophic levels responsible for carrying out various biogeochemical processes and providing ecosystem services. However, forests in Asia are doubly challenged by climate change and air pollution. The rapidly changing air quality, with increasing concentration of greenhouse gases (GHGs), trace gases, volatile organic compounds (VOCs), and ozone (O3 ) also causes global warming leading to climate change, thus jointly creating a challenging condition for the forest ecosystem. The impact on forest ecosystems of the two anthropogenic stressors, viz., climate change and air pollution, requires global attention. These two stressors have been widely studied separately but their combined impact on the forest ecosystem has not been studied extensively, particularly in the Asian region. In this review article, we attempt to explore the importance of interlinking air pollution and climate change impact on Asian forests, by studying the decline of different forest types as a background and markers of forest ecosystem degradation. Our main aim is to understand and summarise the past and ongoing research in this area and to facilitate researchers and policymakers to upgrade their research, policies, and management strategies in the area of integration of air pollution and climate change impact on forest ecosystems in the Asian region.